1983
DOI: 10.1159/000182929
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Lipid Abnormalities in Renal Failure

Abstract: From this study of 163 males and 57 females on maintenance dialysis, evidence is presented that lipid levels, except for cholesterol in females, remain stable for the first 5 years. Thus, baseline lipid classifications are valid through this time period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1
1

Year Published

1987
1987
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 12 publications
(18 reference statements)
1
5
1
1
Order By: Relevance
“…Some studies have found positive correlation between hypertriglyceridemia, plasma cholesterol levels and HD duration,[1315] while others have reported a negative correlation. [11] In the present study, we observed a negative correlation between levels of TGs and duration of HD and confirm that long-term HD treatment has no effect on the levels of TGs.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Some studies have found positive correlation between hypertriglyceridemia, plasma cholesterol levels and HD duration,[1315] while others have reported a negative correlation. [11] In the present study, we observed a negative correlation between levels of TGs and duration of HD and confirm that long-term HD treatment has no effect on the levels of TGs.…”
Section: Discussionsupporting
confidence: 85%
“…Some studies have reported that lipid and lipoprotein compositions do not appear to be influenced by dialysis duration and no relationship exists between plasma TG levels and dialysis duration,[911] whereas others have found correlation between hypertriglyceridemia, cholesterol, lecithin-cholesterol acyltransferase (LCAT) activity and HD duration. [1215]…”
Section: Introductionmentioning
confidence: 99%
“…29], Plasma cholesterol and triglyceride con centrations generally remain stable or may decrease slightly over time in long-term he modialysis patients [52][53][54], Apart from slightly higher concentrations of ApoA-I and ApoE, hemodialysis patients appears to have the same qualitative plasma apoiipoprotein profile as patients before dialysis [ 1], In recent years, the treatment with low-molecularweight heparin for anticoagulation has been introduced. Triglyceride levels may be re duced in some hypertriglyceridemic hemodi alysis patients with certain preparations of low-molecular-weight heparin [55].…”
Section: Effects O F Dialysismentioning
confidence: 99%
“…Determination of lipid and apolipoproteins profile in particular of their abnormalities in patients with chronic terminal renal insufficiency (CTRI) in the early stages of the disease, and analysis of ethiopathogenic mechanisms can significantly help in proposing preventive measures (dietary, treatment) with which there will be reduced visible frequent appearance of dyslipidemia, atherosclerotic lesions and reduced incidence of atherosclerosis in patients with CTRI randomized by gender and age (11). Patients with terminal chronic renal failure (TCRF) mostly appear with the type IV type of secondary hyperlipoproteinemia (according to Frederickson's classification) where high concentrations of triglycerides dominates (hypetriglyceridemia values of 28-100%} (12,13). Apolipoprotein-C3 also known as apo-CIII is a protein that in humans is encoded by the Apo-C3 gene.…”
Section: Introductionmentioning
confidence: 99%